Perancangan User Experience Aplikasi Pendaftaran Bantuan Langsung Tunai UMKM Kota Malang pada Masa Pandemi - Raras Kirana Amaranggana; Ratih Kartika Dewi; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Since August 14, 2020, the government has provided social assistance, namely Direct Cash Assistance for MSMEs, as much as 1.2 million for MSME actors. The submission process is done online through the Google Form, which is managed by the Malang City Cooperative, Industry and Trade Office. However, during the submission process, there were problems such as a lack of information on the Google Form, no follow-up announcement on whether the submission was accepted or not, and some applicants could not access the submission link. So from these various problems, researchers will design a User experience in the Application for Registration of MSMEs in Malang City Cash Direct Assistance. During the Pandemic Period. The method in this study uses the Human-Centered Design (HCD) approach. This method focuses on humans and users who can assist researchers in designing solutions according to user needs and system usability to increase productivity, efficiency, and effectiveness so that people get their satisfaction. In the final stage, the researcher conducted usability testing for five respondents. The result was 100% on the effectiveness aspect, 0.085 goals/second on the efficiency aspect, and 82.5 with the excellent category and scaled A on the user satisfaction aspect. Based on the test results, it can be concluded that the design of the solution that has been designed is acceptable.